2010
DOI: 10.1039/b9nj00696f
|View full text |Cite
|
Sign up to set email alerts
|

Chemical stability and application of a fluorophilic tetraalkylphosphonium salt in fluorous membrane anion-selective electrodes

Abstract: The highly fluorophilic phosphonium salt (R f8 (CH 2 ) 2 )(R f6 (CH 2 ) 2 ) 3 P + I À , 1, was used to provide cationic sites for anion-selective electrodes based on fluorous sensing membranes. The electrodes exhibited the theoretically expected ''Nernstian'' response slopes, and their selectivities for different anions were determined. For environmental analysis, the selective detection of perfluorooctanesulfonate and perfluorooctanoate is of particular interest. While previously reported electrodes based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…Previous work from our group has shown the benefits of using fluorous sensing membranes that consist of fluorous plasticized polymer matrixes doped with fluorophilic ionophores, ionic sites, and electrolytes . We found that fluorous systems exhibit substantially improved ion selectivities as compared to non‐fluorous ISE membranes, which has also resulted in remarkably low detection limits .…”
Section: Introductionmentioning
confidence: 72%
“…Previous work from our group has shown the benefits of using fluorous sensing membranes that consist of fluorous plasticized polymer matrixes doped with fluorophilic ionophores, ionic sites, and electrolytes . We found that fluorous systems exhibit substantially improved ion selectivities as compared to non‐fluorous ISE membranes, which has also resulted in remarkably low detection limits .…”
Section: Introductionmentioning
confidence: 72%
“…The fluorophilic salts bis(tris[(perfluorohexyl)propyl]phosphine)iminium chloride ( 1 ) and sodium tetrakis[3,5-bis(perfluorohexyl)phenyl]borate ( 2 ) were used to provide for cationic and anionic sites, respectively. In comparison to salts of fluorophilic cations used in previous potentiometric studies, the bis(triphenylphosphoranylidene)ammonium cation of 1 has the advantage of a higher chemical stability in the presence of HO – than previously reported fluorophilic phosphonium cations and does not bind coordinatively to analyte anions. Fluorous membranes doped with cationic site 1 did not show any sign of deterioration even when exposed to strongly alkaline solutions, such as 0.1 M NaOH, and exhibited no more interference from OH – than expected for a nonspecific ionophore-free ion exchanger membrane with Hofmeister selectivity (see also p 1595 of ref ).…”
Section: Resultsmentioning
confidence: 91%
“…[39] Although it could be argued that the tetran-butylammonium is not the usual counterion to appear in Nature or bio-related applications, it is noteworthy that the sodium or any other salts may also be used either directly, as shown on the differentiation urine samples based on electrolyte content or in conjunction with tetrabutylammonium (TBA) perchlorate additive that acts as an ion-exchanger commonly used in ion-selective electrodes for anions. [35,44] Each of the individual polymerprobe sensors displays a different response to the anions. This is due to the probe-anion interaction as well as to different distribution of hydrophilic and hydrophobic domains within PUs, a feature that is easy to adjust by using a different proportion of comonomers during the polymer synthesis.…”
Section: Resultsmentioning
confidence: 99%